Realizing pure spin current by the photogalvanic effect in armchair graphene nanoribbons with nano-constriction engineering. Issue 4 (12th January 2023) - Li, Yuejun; Shang, Xiaofei; Zhou, Yan-Hong; Zheng, Xiaohong
Abstract : Pure spin current for a structure with C s symmetry (D1) can be obtained only at certain angles, while for a structure with spatial inverse symmetry (D2), it is robustly independent of the polarization angle. Abstract : We propose nano-constriction engineering of armchair graphene nanoribbons (AGNRs) to construct photoelectric nanodevices aiming to generate pure spin currents through the photogalvanic effect (PGE) using first-principles calculations. Two devices with different symmetries were designed, one by introducing only one isosceles zigzag triangle defect on the lower edge of the central region ('D1') and the other by two symmetrically distributed isosceles zigzag triangle defects on the two edges ('D2'). The results show that pure spin current without accompanying charge current can be generated in both junctions, but with a big difference that pure spin current can be generated only at special polarization angles θ = 0°, 90° and 180° in device D1, while it can be generated at any polarization angle in D2. The robustness in D2 is attributed to the spatial inversion symmetry in geometry and the inversion antisymmetry of spin density. These findings suggest that local magnetism engineering provides a reliable method for generating robust pure spin currents with the PGE in nonmagnetic systems, especially opening up new possibilities for the application of AGNRs in spintronics.